The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1051/e3sconf/202128407029
|View full text |Cite
|
Sign up to set email alerts
|

The impact of budget transparency on tax compliance

Abstract: The article analyzes the factors influencing tax evasion: the value of gross domestic product per capita, tax burden, corruption and openness of information on the use of budgetary funds. The correlation model includes the analysis of two groups of indicators. The first group is indicators of the individual level: education, socio-economic status, attitude to religion, gender, etc. The second group is indicators of the global or national level: GDP per capita, tax burden, the level of corruption in the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…The results showed that taxpayers believed that GEF and TAT could influence government attitudes. The outcome confirmed previous research that discovered positive effects between government effectiveness, tax authority transparency and government attitude (Chindengwike & Kira, 2021;Chisadza et al, 2021;Omotoye et al, 2021;Zvereva et al, 2021). The fiscal illusion theory in tax compliance also supported the findings from previous studies (Martinez-Vazquez, Harwood & Larkins, 1992;Nkundabanyanga et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results showed that taxpayers believed that GEF and TAT could influence government attitudes. The outcome confirmed previous research that discovered positive effects between government effectiveness, tax authority transparency and government attitude (Chindengwike & Kira, 2021;Chisadza et al, 2021;Omotoye et al, 2021;Zvereva et al, 2021). The fiscal illusion theory in tax compliance also supported the findings from previous studies (Martinez-Vazquez, Harwood & Larkins, 1992;Nkundabanyanga et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Research in the past has measured the impact of corporations concerning government attitude; however, this study used individuals. Government effectiveness (Chisadza et al, 2021;Omotoye et al, 2021) and Tax authority transparency (Chindengwike & Kira, 2021;Zvereva et al, 2021) were found in these study, as predicators of voluntary tax compliance. Thus, forming the dependent variable and the independent variable of government attitude.…”
Section: Conceptual Frameworkmentioning
confidence: 51%
See 2 more Smart Citations
“…Indeks demokrasi disajikan dengan skala 0-10, semakin tinggi nilainya mencerminkan semakin baik demokrasi di negara tersebut. Zvereva et al, (2021) menemukan bahwa transparansi anggaran yang merupakan salah satu ciri demokrasi berpengaruh positif terhadap kepatuhan pajak.…”
Section: Variabel Penelitianunclassified